THU0207 The effect of the use of glucocorticoids on health assessment questionnaire in patients with rheumatoid arthritis in clinical remission –data from kansai consortium for well-being of rheumatic disease patients (answer cohort)-. (15th June 2017) - Hara, R; Fujimura, T; Hashimoto, M; Furu, M; Yamamoto, W; Hirano, T; Ebina, K; Yoshida, S; Nagai, K; Amuro, H; Son, Y; Onishi, T; et al.
Abstract : Background: In the treatment of patients with rheumatoid arthritis (RA), glucocorticoids (GCs) with csDMARDs remain an important treatment option given their capacity to increase clinical, structural and functional efficacy. On the other hand, it is reported that GCs usage even at low dosage significantly deteriorated functional capacity in patients with low disease activity state. In these previous study, disease activity and subsequent joint destruction have no small influence on functional disability. Objectives: To investigate the effect of the use of glucocorticoids (GCs) in patients with RA who had maintained clinical remission on functional ability. Methods: Among 2, 649 patients with RA who achieved DAS-ESR<2.6 after 2013 in the multi-center cohort, 1, 171 patients who had maintained DAS-ESR<2.6 were eligible. Clinical and demographic characteristics were collected at baseline. We calculated odds ratio (OR) (95% confidence interval) of the use and dose of GCs to predict the yearly progression of HAQ-DI score adjusted for age, sex, BMI, disease duration, RF titer, ACPA titer, CRP, MMP-3, DAS28-ESR, HAQ-DI, use of MTX and use of biologic DMARDs as covariates in multiple logistic regression model. Results: Characteristics of patients at baseline were as follows (median (IQR), proportion). The age was 61 (48–68) years, female was 70.6%, disease duration was 4.5 (1.7–10.7) years, RF-positive was 64.4%, ACPA-positive was 70%, DAS28-ESR was 2.0 (1.6–2.6), HAQ-DI score was 0.125 (0–0.5). Of the 1, 171 patients, 235 (20.1%) patients had been treated with oral GCs when achieving clinical remission. CRP (0.06 (0–0.2) vs 0.03 (0–0.1), p=0.03), MMP-3 (106.1 (73.2–172.8) vs 49.5 (36.5–77.2), p<0.001), SDAI (2.9 (1.5–5.9) vs 2.6 (1.0–4.8), p=0.003), DAS28-CRP (1.6 (1.3–2.0) vs 1.5 (1.2–1.9), p=0.008), patients' global assessment (mm) (15 (5–31) vs 11 (3–25), p=0.006), physicians' global assessment (mm) (6 (3–12) vs 5 (0–10), p=0.001) and HAQ-DI (0.38 (0–0.88) vs 0.13 (0–0.38), p<0.001) were significantly higher and disease duration was significantly longer (year) (8.9 (3.2–19.6) vs 4.1 (1.6–9.3), p<0.01) in the GCs group compared to the non-GCs group. One hundred and fifty-eight (67.2%) patients had been treated with GCs during follow up, and median dose was 4.5 (2.5–5.5) mg/day. Two hundred and eighty-seven (24.5%) patients' yearly change of HAQ-DI score incresed. The adjusted OR of the use of GCs at baseline was 2.06 (1.21–3.51). The adjusted OR of the daily dose of GCs <5mg was 1.61 (0.73–3.56), whereas that of GCs≧5mg was 2.65 (1.11–6.34) in patients with keeping GCs use. Conclusions: The use of GCs in RA patients with sustained remission was the risk factor of progression of HAQ-DI score dose-dependently. Disclosure of Interest: None declared